The Effect of Workplace Stretching Exercise (WSE) Interventions on Nurse's Musculoskeletal Complaints at Health Services in Bengkulu - Mardiani Mardiani; Maksuk Maksuk; Husni Husni; Widia Lestari; Aishath Hamid (International Journal of Advanced Health Science and Technology, 2022)
Musculoskeletal complaints are the most common complaints experienced by nurses in health services. This condition is caused by several factors including nurses' work attitude, length of work, work shifts, and type of work. The purpose of this study was to analyze the effect of giving muscle stretching exercises to reduce musculoskeletal complaints in nurses at Bengkulu City Health Services. This study was a quasi-experimental research design with a pre and post-test approach with a control group design. The population of this study were nurses in Bengkulu City health services. The sampling method was consecutive sampling. The research sample was 60 respondents divided into 30 respondents in the treatment group and 30 respondents in the control group. The analysis used Paired sample t-test and an independent sample t-test with 0.05. The results of the analysis showed a significant 2-way p-value of 0.000 <0.05, so there was a significant difference between the control and treatment groups. So, it can be concluded that there was a decrease in musculoskeletal complaints in nurses at the Bengkulu City Health Center after being given the Workplace Stretching Exercise (WSE) intervention which was more effective in the treatment group than in the control group.